Electromyographic Comparison of an Abdominal Rise on a Ball with a Traditional Crunch - Aleš Dolenec; Mojca Svetina; Vojko Strojnik (Sensors, 2022)
We propose a new exercise, the abdominal rise on the ball, to replace the traditional crunch in exercise programs. The aim of this study is to compare the activity of the abdominal muscles when performing an ARB with the same activity when performing a traditional crunch. Twenty healthy adults participated in the study. Surface electromyography (EMG) was recorded from the upper and lower rectus abdominis (URA, LRA), internal oblique (IO), external oblique (EO), transversus abdominis (TrA), and erector spinae (ES). EMG values were normalized to maximal voluntary isometric contraction. A paired t-test, nonparametric Wilcoxon test and correlation coefficient were used for statistical analysis. The normalized EMG values of EO, TrA and ES, were statistically significantly higher during the abdominal rise on the ball compared to the traditional crunch, while URA, LRA and IO were significantly lower during the abdominal rise on the ball compared to the traditional crunch. TrA, EO and IO are sufficiently activated during an abdominal rise on a ball, so the exercise could be deemed effective for strengthening these muscles.